Ontogeny, functions and reprogramming of Kupffer cells upon infectious disease - Musrati, Mohamed Amer; De Baetselier, Patrick; Movahedi, Kiavash; Van Ginderachter, Jo A. (Frontiers in Immunology, 2023)
The liver is a vital metabolic organ that also performs important immune-regulatory functions.In the context of infections, the liver represents a target site for various pathogens, while also having an outstanding capacity to filter the blood from pathogens and to contain infections.Pathogen scavenging by the liver is primarily performed by its large and heterogeneous macrophage population. The major liver-resident macrophage population is located within the hepatic microcirculation and is known as Kupffer cells (KCs). Although other minor macrophages reside in the liver as well, KCs remain the best characterized and are the best wellknown hepatic macrophage population to be functionally involved in the clearance of infections. The response of KCs to pathogenic insults often governs the overall severity and outcome of infections on the host. Moreover, infections also impart long lasting, and rarely studied changes to the KC pool. In this review, we discuss current knowledge on the biology and the various roles of liver macrophages during infections. In addition, we reflect on the potential of infection history to imprint long-lasting effects on macrophages, in particular liver macrophages.The liver harbors a large and heterogeneous population of resident macrophages (Figure 1).Work on mouse models has generated extensive information on the major resident macrophage